A Study on Effect of Temperature on Lubricating Oil Using Bare and Bent Optical Fibre Sensor: A Theoretical and Experimental Approach - Bordoloi, S; Laskar, S (International Journal of Computer Sciences and Engineering, 2025)
This paper describes a bare and bent multimode optical fibre sensor to study the effect of temperature on a pure lubricating oil sample. It describes both mathematical and experimental analysis of the oil sample when subjected to high temperature. The sensor system consists of (i) a bare and bent multimode optical fibre (BBMOF) sensor (ii) LM35 temperature sensor (iii) microcontroller system for sampling of data. The BBMOF is immersed in a lubricating oil sample and subjected to varying temperature. The BBMOF is used to measure the refractive index (RI) of the oil sample and the LM35 is used to provide the measure of temperature of the lubricating oil sample. The measure of the refractive index (RI) and temperature are sampled by an ATmega 32 microcontroller based system for processing and further analysis of measured data.